2023
DOI: 10.3389/fonc.2023.1279487
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative inflammation and nutrition-based comprehensive biomarker for predicting prognosis in resectable colorectal cancer

Hao Cai,
Jiancheng Li,
Yu Chen
et al.

Abstract: BackgroundColorectal cancer (CRC) remains a major global health concern, with significant morbidity and mortality rates. In this study, we aimed to develop a comprehensive blood indicator based on systemic inflammation and nutritional condition to predict the prognosis of resectable CRC patients.MethodsA retrospective cohort of 210 CRC patients who underwent radical resection at the First Affiliated Hospital of Chongqing Medical University, China, between January 2015 and December 2017, was included in the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Zhang et al [ 38 ] and He et al [ 39 ] proposed SII as a good biomarker for diagnosing gastric cancer compared with NLR and PLR, highlighting its significant correlation with OS in this setting. It has been shown that SIRI predicts patient prognosis in a variety of cancer types[ 40 , 41 ]. In our hospital, the study of lymphocyte subpopulations further affirmed their role as predictive biomarkers for gastric cancer, surpassing the predictive capability of inflammatory biomarkers[ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 38 ] and He et al [ 39 ] proposed SII as a good biomarker for diagnosing gastric cancer compared with NLR and PLR, highlighting its significant correlation with OS in this setting. It has been shown that SIRI predicts patient prognosis in a variety of cancer types[ 40 , 41 ]. In our hospital, the study of lymphocyte subpopulations further affirmed their role as predictive biomarkers for gastric cancer, surpassing the predictive capability of inflammatory biomarkers[ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative malnutrition in patients with CRC is associated with many postoperative complications and overall poor prognosis. 57 Because NHB patients are more likely to reside in food-desert neighborhoods, 40 it might be advantageous to administer nutritional screenings and provide patient-education related to presurgical nutrition.…”
Section: Biopsychosocial Factors Associated With Outcomes In Colorect...mentioning
confidence: 99%
“…Complete blood count-based biomarkers have been shown to correlate well with clinical outcomes in numerous chronic [ 5 , 6 , 7 , 8 , 9 , 10 ], infectious [ 11 , 12 , 13 , 14 , 15 ], and surgical conditions [ 16 , 17 , 18 , 19 , 20 ], as well as in cancer [ 21 , 22 , 23 , 24 , 25 , 26 ]. In particular, the potential role of the red cell distribution width (RDW), a biomarker of the heterogeneity of red blood cells’ size, in predicting adverse events and survival currently represents a topic of intense research in numerous clinical conditions [ 27 , 28 ], including malignancies such as colorectal cancer [ 29 , 30 , 31 ], esophageal cancer [ 32 , 33 ], lung cancer [ 34 , 35 ], breast cancer [ 36 , 37 ], and other malignancies [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%